Investigation and Evaluation of Corneal Parameters in Patients with Thyroid Ophthalmopathy - Ulas, Burak; Ozcan, Altan Atakan (Scientific Reports in Medicine, 2025)
Objective: To evaluate corneal findings in patients with thyroid ophthalmopathy (TO) according to clinical activity score using corneal densitometry and corneal topography parameters. Methods: This cross-sectional study was conducted in the department of Ophthalmology of Cukurova University between January 1, 2021, and June 31, 2022. The patients underwent a comprehensive ophthalmological examination, including best-corrected visual acuity, slit lamp biomicroscopy, intraocular pressure measurement with Goldmann applanation tonometry, fundoscopic examination, and hertel exophthalmometry. Clinical activity scores according to the European Group of Graves’ Orbitopathy (EUGOGO) classification and retinal nerve fiber layer values were also recorded. Corneal densitometry and topography data recorded for 3 months were noted, and evaluated together according to the EUGOGO classification. Results: Fifty eyes of 25 thyroid ophthalmopathy cases (15 female, 10 male) with a mean age of 52.6±12.87 years were included in the study. For corneal densitometric measurements in the first month of evaluation, there were significant differences in 2-6 mm zone specifically in anterior and posterior layers (p<0,040, p<0,010), 6-10 mm zone specifically in anterior, center, posterior layers and total diameter (p<0,008, p<0,002, p<0,002, p<0,003). When it comes to corneal topography, changes were detected in Sim K values especially a decrease in K1 and Avg in patients with mild and severe TO (p<0,046, p<0,010) and in patients with mild and moderate TO (p<0,027, p<0,017). During the third month the retinal nerve fiber layer values were significantly thinner in patients with moderate-severe TO (p<0,029). Conclusion: Mechanical and inflammatory factors play a significant role in the ocular findings...